Comparison of water sorption and solubility of Acropars and Meliodent heat cure acrylic resins - Golbidi F; Taherian A (Tehran University of Medical Sciences, 2006)
Background and Aim: Water sorption and solubility are important properties of acrylic resins. Denture base acrylic resins have low solubility. This solubility results from the leaching out of unreacted monomer and water soluble additives into the oral fluids. The solubility of denture bases can cause oral soft tissue reactions. In addition, water absorbed into this material acts as a plasticizer and decreases the mechanical properties such as hardness, transverse strength, fatigue limit and also can change the color and dimensional stability. The aim of this study was to compare the water sorption and solubility of Acropars and Meliodent heat cure acrylic resins. Materials and Methods: This experimental study was performed on the basis of ADA specification No.12 and ISO No.1567 and standards NO: 2571 of Institute of Standards & Industrial Research of Iran. Six disc form samples of each acrylic resin were prepared, with the dimension of 50×0.5 mm. After desiccating, the samples were kept in an oven for 24 hours and weighed. Then they were immersed in water, kept in oven for 7 days and weighed again. After this phase, the samples were carried to a dessicator, for 24 hours and kept in an oven for drying and were weighed for the third time. Data were analyzed with Mann Whitney and one sample t-test. P<0.05 was considered as the limit of significance. Results: Water sorption mean values were 30.5±0.1 µg/mm3 or 0.76±0.01 mg/cm2 for Meliodent samples and 30.7±0.87 µg/mm3 or 0.77±0.009 mg/cm2 for Acropars samples. No significant difference was observed in water sorption of these two materials (P=0.9). Meliodent acrylic resin showed lower solubility (1.7±0.097 µg/mm3 or 0.042±0.001 mg/cm2) than Acropars acrylic resin (2.5±0.13 µg/mm3 or 0.062±0.001 mg/cm2) (P=0.002). Conclusion: Acropars heat cure acrylic resin matched well with the requirements of the international standards for water sorption, but its solubility was not favorable. This problem is probably the result of high concentration of residual monomer, the amount and type of cross linking agents and plasticizers as well as the amount of water soluble additives in this material.